A Home away from Home? - van Ringelesteijn, Lisanne Marinda (UiT Norges arktiske universitet, 2024)
This thesis is part of a bigger project, and, together with the film A Home Away From Home (2024), illustrates different ways in which Dutch people experience living in northern Norway and how they engage in home-making practices. The study explores the ways in which they engage in home-making practices to create a home for themselves, while also reflecting on their sense of belonging. The research can be placed in a broader context within anthropological debates on migration and ‘home’. Through employing different qualitative research methods, such as participant observation, semi-structured interviews, and making use of the film camera, this thesis aims to argue that Dutch migrants in Norway engage in home-making practices through engaging in (new) hobbies, creating networks, embodying the environment, learning the language, and adapting to a new culture, which also evoke feelings of belonging. All while reflecting on their identity as a Dutch person in northern Norway. Moreover, the study analyses the role of memories of an old home in creating a new one, together with exploring the transnational ties that Dutch migrants sustain in both the Netherlands and Norway.